GAME PETUALANGAN KH. ZAINAL MUSTHAFA SEBAGAI MEDIA PENGETAHUAN SEJARAH TASIKMALAYA UNTUK REMAJA - Fernida, Yandi; Supriatman, Agus; Sumaryana, Yusuf (Institut Teknologi dan Bisnis Swadharma, 2024)
Today's teenagers lack understanding of local history, one of which is the history of Tasikmalaya, which is very unfortunate because by understanding history, you can better know and appreciate the struggles of figures in that history. From the background stated, the aim was formulated, namely to create a game application